2020
DOI: 10.1101/2020.07.02.20145441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of IgG and IgM antibodies to SARS-CoV-2 among clinic staff and patients

Abstract: The coronavirus disease 2019 (COVID-19) is now a pandemic with devastating social and economic consequences. The extent of the spread of COVID-19 within populations is uncertain since diagnostic tests have not been carried out on all eligible persons and doing such diagnostic tests on everyone is much less feasible in developing countries such as Nigeria. Tests for antibodies to SARS-CoV-2, the virus that causes COVID-19, are more affordable, readily available, and require minimal training than current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a study conducted in Kenya from April to June 2020 on 3,174 blood donors’ samples, seroprevalence was 5.2% (95%CI: 3.7%-7.1%) 7 . In two small populations of household contacts and healthcare workers in Nigeria, seroprevalence rates rise to 25.4% and 45% respectively 8,9 . Among the available pre-print or published studies, seroprevalence was evaluated using Rapid Diagnostic Tests (RDTs) in three studies, enzyme-linked immunosorbent assay (ELISA) in three studies and Clinical Laboratory Improvement Amendments (CLIA) in one study 612 .…”
Section: Discussionmentioning
confidence: 97%
“…In a study conducted in Kenya from April to June 2020 on 3,174 blood donors’ samples, seroprevalence was 5.2% (95%CI: 3.7%-7.1%) 7 . In two small populations of household contacts and healthcare workers in Nigeria, seroprevalence rates rise to 25.4% and 45% respectively 8,9 . Among the available pre-print or published studies, seroprevalence was evaluated using Rapid Diagnostic Tests (RDTs) in three studies, enzyme-linked immunosorbent assay (ELISA) in three studies and Clinical Laboratory Improvement Amendments (CLIA) in one study 612 .…”
Section: Discussionmentioning
confidence: 97%
“… 7 In two small populations of household contacts and healthcare workers in Nigeria, seroprevalence rates were to 25.4% and 45%, respectively. 8 , 9 Among the available preprint or published studies, seroprevalence was evaluated using RDTs in three studies, ELISA in three studies, and Clinical Laboratory Improvement Amendments in one study. 6 12 A recent study aiming to detect the persistence of SARS-CoV-2 antibodies 3–4 months after the onset of symptoms in healthcare workers at the Strasbourg University hospital reported that ELISA serological test has a 59% sensitivity and Biosynex RDT a 85% sensitivity compared with the S-flow reference test developed by the French National Reference Center for SARS-CoV-2 infection (Pasteur Institute, Paris, France).…”
Section: Discussionmentioning
confidence: 99%
“…Populationbased serological surveys, hundreds of which have been conducted worldwide, can help shed light on the extent of this underestimation of SARS-CoV-2 infections (5,6). As of March 18, 2021, only 16 studies published or available in preprint had been conducted in sub-Saharan Africa (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) H. Majiya et al, unpub. data,…”
mentioning
confidence: 99%